Situating Poetry : Covenant and Genre in American Modernism - Wall, Joshua Logan (Book collections on Project MUSE., 2022)
In this unique account of American modernist poetics, religious pluralism creates a lens through which to consider the bounds of solidarity and division within and among ethnic identities and their corresponding literatures.